EDUKASI DAN SOSIALIASI BAHAYA JUDI ONLINE PADA SISWA SMP DAN SMK DWI PANGGA SEBAGAI BENTUK PENGABDIAN PADA MASYARAKAT - Iin Yulianti; Annisa Septri Ananda; Amanda Aulia Kusuma; Alvina Salsabila; Mardiana Putpita Sari (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
The development of digital technology has led to a rise in online gambling practices among teenagers, particularly junior and vocational high school students. Low digital literacy and lack of supervision make them a vulnerable group. In response, KKN (Community Service Program) students conducted a socialization program at SMP and SMK Dwi Pangga in Bandar Lampung as a form of community engagement. The activities included interactive lectures, discussions, and quiz-based evaluations, covering topics such as the definition of online gambling, its negative impacts, and prevention strategies. The results showed that student participation exceeded the target, with high enthusiasm and improved understanding of online gambling risks. The interactive method proved effective in delivering educational messages, while also highlighting the role of university students as agents of change in preventing deviant behavior among teenagers.